2023
DOI: 10.1097/ms9.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular platelet-rich plasma vs. corticosteroid injections efficacy in knee osteoarthritis treatment: a systematic review

Abstract: Background: Osteoarthritis (OA) affects the entire joint structure. The most injured joints are the hands, knees, and hips. OA is a common disease all over the world, and a cause of disability in the elderly; hence, medicine is facing a steady challenge to find effective therapeutics to relieve the pain, improving symptoms for a better quality of life for patients. Purpose: To compare the results, in the recent literature, of intra-articular injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A study that was performed in Ireland suggested a similar role of PRP and CSs in the treatment of KOA [4]. A systemic review also suggested that PRP effects on KOA management last longer than CSs [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study that was performed in Ireland suggested a similar role of PRP and CSs in the treatment of KOA [4]. A systemic review also suggested that PRP effects on KOA management last longer than CSs [9].…”
Section: Discussionmentioning
confidence: 99%
“…Greater scores indicate more pain, more joint stiffness, and more limitation in joint function; lower values indicate less pain, stiffness in the joints, and limitation in joint function. International studies have also employed WOMAC and VAS [ 9 , 10 ]. In the second section of the proforma, information about the grade of KOA and the side of the affected knee was also recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain relievers and nonsteroidal anti-inflammatory drugs (NSAIDs) reduce pain and inflammation in osteoarthritis ( Ouyang et al, 2023 ). For example, acetaminophen, ibuprofen, naproxen, corticosteroid injection, and hyaluronic acid injection, have been used to reduce pain and inflammation in osteoarthritis ( Shentu et al, 2022 ; Goyal et al, 2023 ; Idres and Samaan, 2023 ; Richard et al, 2023 ). Exercise, weight management, and physical therapy are useful for osteoarthritis patients ( Spanoudaki et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%